2014
DOI: 10.1093/femsec/fiu021
|View full text |Cite
|
Sign up to set email alerts
|

Drying effects on archaeal community composition and methanogenesis in bromeliad tanks

Abstract: Tank bromeliads are highly abundant epiphytes in neotropical forests and form a unique canopy wetland ecosystem which is involved in the global methane cycle. Although the tropical climate is characterized by high annual precipitation, the plants can face periods of restricted water. Thus, we hypothesized that water is an important controller of the archaeal community composition and the pathway of methane formation in tank bromeliads. Greenhouse experiments were established to investigate the resident and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 75 publications
4
23
1
Order By: Relevance
“…In former studies this TRF was assigned to the hydrogenotrophic methanogens Methanomicrobiales or Methanocellales (Brandt et al 2014;Martinson et al 2010). The methanotrophic community was dominated by a 245-bp TRF (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In former studies this TRF was assigned to the hydrogenotrophic methanogens Methanomicrobiales or Methanocellales (Brandt et al 2014;Martinson et al 2010). The methanotrophic community was dominated by a 245-bp TRF (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Carbon availability was already identified as one of the main drivers of microbial community structure in soil (Fierer et al 2003) and Lopez et al (2009) assumed that occasional organic matter inputs can induce a eutrophic condition in tank-bromeliads. In a previous study by Goffredi et al (2011b) it was shown that pH has an effect on the bacterial community composition and that a low water content and therefore an increased oxygen exposure, affected the bacterial and archaeal community composition in tank bromeliad slurry (Brandt et al 2014;Brandt 2015). In the present study, the microbial communities were further sorted along nitrogen concentrations in the tank slurry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations